Reassessing the out‐of‐phase phenomenon in shake flasks by evaluating the angle‐dependent liquid distribution relative to the direction of the centrifugal acceleration. Issue 11 (6th September 2019) - Amizon, Azizan; Sieben, Michaela; Wandrey, Georg; Büchs, Jochen
Abstract: Shake flasks are still the most relevant experimental tool in the development of viscous fermentation processes. The phase number, which defines the onset of the unfavorable out‐of‐phase (OP) phenomenon in shake flasks, was previously defined via specific power input measurements. In the OP state, the bulk liquid no longer follows the orbital movement of the imposed centrifugal force, which is for example, detrimental to oxygen transfer. In this study, an optical fluorescence technique was used to measure the three‐dimensional liquid distribution in shake flasks. Four new optically derived evaluation criteria for the phase transition between the in‐phase and OP condition were established: (a) thickness of the liquid film left on the glass wall by the rotating bulk liquid, (b) relative slope of the leading edge of bulk liquid (LB) lines, (c) trend of the angular position of LB, and (d) very high angular position of the leading edge. In contrast to the previously applied power input measurements, the new optical evaluation criteria describe the phase transition in greater detailed. Instead of Ph = 1.26, a less conservative value of Ph = 0.91 is now suggested for the phase transfer, which implies a broader operating window for shake flask cultivations with higher viscosities. Abstract : Shake flasks are still the most relevant experimental tool in the development of viscous fermentation processes. The phase number, which defines the onset of the unfavorable out‐of‐phase phenomenon in shake flasks, was previously defined via specific power input measurements.